“When in Rome…”: structural determinants impacting healthcare access, health outcomes, and well-being of South Asian older adults in Ontario using a multilingual qualitative approach - Chowdhury, Diya; Tong, Catherine; Lopez, Kimberly; Neiterman, Elena; Stolee, Paul (Frontiers in Public Health, 2024)
With the increase in international migration, the need for an equitable healthcare system in Canada is increasing. The current biomedical model of healthcare is constructed largely in the Eurocentric tradition of medicine, which often disregards the diverse health perspectives of Canada’s racialized immigrant older adults. As a result, current healthcare approaches (adopted in the US and Canada) fall short in addressing the health needs of a considerable segment of the population, impeding their ability to access healthcare services. This study aimed to identify and understand the structural and systemic factors that influence healthcare experiences and well-being among South Asian older adults in Ontario, addressing a significant gap in empirical and theoretical knowledge in the Canadian context. We conducted in-depth individual and dyadic interviews (n = 28) utilizing a descriptive multilingual cross-cultural qualitative approach. Through this research, participants expressed that their understanding of well-being does not align with that of their healthcare providers, resulting in unmet health needs. Our study uses an intersectional lens to demonstrate participants’ perceptions of virtual access to care and systemic factors, such as mandatory assimilation and whiteness as a taken-for-granted norm impacting the health and well-being of South Asian older adults. The findings of this research can offer valuable insights to healthcare providers and policymakers in developing culturally competent practices, guidelines, and training policies that effectively address the healthcare needs of the South Asian population in Canada.